LEGAL BOUNDARIES OF SOCIAL RELATIONS BETWEEN CIVIL SOCIETY AND JUDICIAL BODIES - Mariia Blikhar; Radoslav Jankal (Соціально-економічні відносини в цифровому суспільстві, 2024)
The evaluation procedure of the judiciary in the modern conditions of the relationship between civil society and the rule of law occupies a key place because the modern conditions for the formation of such relationships emphasize the struggle for the rule of law and the independence of judges. Within the framework of the study, it was found that the relationship between civil society and the rule of law implements the established system of checks and balances in ensuring the balance of social relations (including the recognition of lawful behavior as a perceived necessity) in general and the protection of individuals from the arbitrariness of authorities in particular. Therefore, in this context, the influential importance of the judiciary is given its ability to fully protect the violated rights of the individual and the interests of the state within the framework of the legal field. At the same time, it is necessary to state that the state and civil society, within the limits of their mutual relations, have certain regulatory and control functions regarding the activities of the judiciary. In such a case, the relationship between the state and civil society within the framework of the evaluation procedure of the judiciary's activity should be interpreted as a system that performs specific functions in order to characterize the presence of interconnected elements with clearly defined forms of relationships. At most, these relationships contain a number of specific elements, among which are the following: subjects of interaction, objects of interaction, mutual relations between subjects, and changes caused by the interaction of subjects. It is substantiated that the key feature of the court within the framework of the relationship between civil society and the rule of law is primarily the independence of the court through the independence of judges. The definition of the concept of "independent judge" is proposed, according to which such a judge is a highly qualified specialist who in his practical activities acts exclusively on the basis of the law, making unbiased legal decisions, relying on the requirements of regulatory legal acts, regardless of possible benefit for himself. In turn, the relationship between civil society and judicial authorities has a direct impact on increasing the efficiency of court work through the establishment of the principle of the rule of law, helping to ensure the independence of judges on the one hand, and increasing the level of legal awareness and legal culture of the population on the other hand.